Refreshing composition based on plant essential oil and preparation method thereof
By using a three-layer composite delivery system and a multi-layered gel network, the problems of volatility, degradation and stability of plant essential oil products are solved, achieving precise controlled release and long-lasting refreshing effects, and improving the loading efficiency and usage time of essential oils.
Patent Information
- Application Number
- CN202511374409.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2025-10-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing plant essential oil products suffer from problems such as high volatility, easy degradation of active ingredients, difficulty in loading and releasing components with different polarities, and poor stability during use. They also lack precise control over release, resulting in short-lasting effects.
A three-layer composite delivery system is adopted, including an ion gel sustained-release base layer, a plant-derived emulsifier composite biphase system, and a photoprotection and antioxidant protective layer. Through gradient cross-linking network and hydrophilic differential separation technology, the three-stage essential oil delivery is achieved. Combined with plant-derived light shielding agents and free radical scavengers, a multi-layered gel network is constructed.
It significantly improves the stability and release efficiency of essential oil active ingredients, increases the retention rate of active ingredients, prolongs the release time, and improves the loading efficiency, achieving precise controlled release and long-lasting refreshing effects.
Smart Images

Figure CN120859987A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of plant essential oil products technology, and more specifically, to a refreshing composition based on plant essential oils and its preparation method. Background Technology
[0002] Plant essential oils are widely used in daily life and work environments due to their natural, green, and safe properties. Existing technologies, such as patent documents CN102846622A and CN108687077A, disclose some compound preparations of plant essential oils, but most of them use a single carrier system. Currently, common plant essential oil-based stimulant products on the market mainly exist in the form of sprays, sachets, and essential oil diffusers.
[0003] However, these traditional products face several technical obstacles during use: essential oil components are highly volatile, leading to rapid loss of active ingredients and difficulty in maintaining their effects; active components in essential oils are easily degraded under light conditions, especially ultraviolet and visible light radiation, which have a significant destructive effect on terpenes, esters, and other active components; essential oil components have large polarity differences, making it difficult to effectively load and release components with different hydrophilicities in the same carrier system; traditional essential oil delivery systems lack the ability to precisely control the release process, making it impossible to achieve on-demand and progressive release; and essential oil products have poor stability under high temperature and high humidity conditions, with active ingredients easily oxidizing and deteriorating. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a refreshing composition based on plant essential oils and its preparation method.
[0005] A refreshing composition based on plant essential oils, comprising the following ingredients in parts by weight: 20-30 parts menthol, 10-15 parts borneol, 10-15 parts lime oil, 8-12 parts patchouli oil, 8-12 parts lavender oil, 8-12 parts basil, 7-11 parts geranium oil, 3-7 parts clove oil, and 3-7 parts eucalyptus leaf oil;
[0006] The composition also includes a three-layer composite delivery system, a plant-derived emulsifier composite biphase system, and a protective and antioxidant protective layer;
[0007] The three-layer composite delivery system includes: an ion gel sustained-release base layer, which is formed by cross-linking natural polysaccharides with multivalent metal ions and has a gradient distribution of cross-linking degree from the surface to the interior;
[0008] The plant-derived emulsifier composite biphase system includes an aqueous phase and an oil phase, wherein the hydrophilic essential oil component is loaded in the aqueous phase and the hydrophobic essential oil component is loaded in the oil phase;
[0009] The photoprotection and antioxidant protective layer includes a light shielding layer, a free radical scavenging layer, and an antioxidant layer. The light shielding layer contains a plant-derived light shielding agent, the free radical scavenging layer contains a plant-derived free radical scavenger, and the antioxidant layer contains a plant-derived antioxidant.
[0010] Preferably, the natural polysaccharide is selected from sodium alginate, chitosan, and combinations thereof; the multivalent metal ion is selected from calcium ion, zinc ion, and combinations thereof.
[0011] Preferably, the crosslinking degree gradient distribution of the iontophoresis sustained-release base layer is as follows: the surface crosslinking degree is 30-40%, and the internal crosslinking degree is 70-80%.
[0012] Preferably, the plant-derived emulsifier in the plant-derived emulsifier composite two-phase system is selected from saponins, lecithin, protein hydrolysates, sucrose fatty acid esters, and combinations thereof.
[0013] Preferably, a secondary network structure is formed within the plant-derived emulsifier composite biphase system, constituting a "network within a network" hierarchical sustained-release system.
[0014] Preferably, the plant-derived light-shielding agent includes anthocyanins and lycopene; the plant-derived free radical scavenger includes tea polyphenols and rosemary extract; and the plant-derived antioxidant includes tocopherols and carotenoids.
[0015] Preferably, the composition achieves a three-stage essential oil delivery mode: a rapid release phase (0-15 minutes) releasing 25±5% of the active ingredients, a sustained release phase (15 minutes-8 hours) releasing 50±5% of the active ingredients, and a deep release phase (8-24 hours) releasing 15±5% of the active ingredients.
[0016] A method for preparing a refreshing composition based on plant essential oils includes the following steps:
[0017] Step 1: Prepare an essential oil-based invigorating composition;
[0018] Step 2: Constructing the ionogel sustained-release base layer, including preparing a natural polysaccharide solution, preparing a polysaccharide-essential oil premix system, and forming a gradient cross-linking network;
[0019] Step 3: Construct a plant-derived emulsifier complex biphase system, including preparing a plant-derived emulsifier complex system, separating and loading essential oil components based on differences in hydrophilicity, forming a biphase microemulsion system, and constructing a multi-layered gel network;
[0020] Step 4: Add a photoprotective and antioxidant protective layer, including the preparation of plant-derived light-shielding agents, plant-derived free radical scavengers and plant-derived antioxidants, and the construction of a multi-layered photoprotective and antioxidant synergistic structure;
[0021] Step 5: Product shaping and packaging.
[0022] Preferably, the method for forming a gradient cross-linked network in step 2 includes: adding the polysaccharide-essential oil premixed system dropwise into a low-concentration metal ion cross-linking solution for surface cross-linking for 10-20 minutes, and then transferring it to a high-concentration metal ion cross-linking solution for deep cross-linking for 20-40 minutes.
[0023] Preferably, the method for separating loaded essential oil components based on hydrophilicity differences in step 3 includes: loading hydrophilic essential oil components with logP<3 into the aqueous phase and loading hydrophobic essential oil components with logP≥3 into the oil phase.
[0024] Preferably, the method for constructing a multi-layered gel network in step 3 includes: using glutaraldehyde to react with amino groups in protein hydrolysates to form a covalent cross-linked network inside the microemulsion droplets, thus constituting a "network within a network" hierarchical system.
[0025] Application of a plant essential oil-based stimulating composition in a stimulating patch.
[0026] The beneficial effects of this invention are as follows:
[0027] Significantly improved stability: The multi-layered light protection and antioxidant synergistic structure enables the product to retain up to 85.7% of the active ingredients of essential oils after 8 hours of simulated sunlight exposure, which is 2.7 times higher than traditional products; after 6 months of storage at room temperature, the retention rate of active ingredients reaches 92.3%, and the structural integrity is maintained at 98.2% under high humidity conditions, which comprehensively solves the technical problems of easy volatility and easy oxidation of essential oils.
[0028] Outstanding precise controlled release effect: The multi-layered gel network realizes a unique three-stage release mode - the rapid release stage (0-15 minutes) releases 25.2% to provide an immediate refreshing effect, the sustained release stage (15 minutes-8 hours) releases 50.1% to maintain stable efficacy, and the deep release stage (8-24 hours) releases 16.2% to extend the duration of action, extending the effective release time from 2-4 hours of traditional products to more than 24 hours.
[0029] Significantly improved loading efficiency: The separation and loading technology based on differences in hydrophilicity enables the average loading rate of essential oil components to reach 96.9%, which is about 32% higher than traditional methods. In particular, the loading efficiency of hydrophobic components is improved more significantly, effectively solving the industry problem of simultaneously and efficiently loading essential oil components of different polarities.
[0030] Extended duration of efficacy: Both subjective evaluations and objective tests have confirmed that the product has an average effective time of 19.5 hours, and can still maintain 85.7% of the attention level after 8 hours of use. The duration of efficacy is 5-10 times longer than that of traditional products. Attached Figure Description
[0031] Figure 1These are the curves showing the changes in the total essential oil component retention rate of the three samples under different light exposure times;
[0032] Figure 2 This is a comparison chart of the loading efficiency of different essential oil components;
[0033] Figure 3 This is a comparison of the essential oil release from the three products. Detailed Implementation
[0034] The subject matter described herein will now be discussed with reference to exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and implement the subject matter described herein, and changes may be made to the function and arrangement of the elements discussed without departing from the scope of this specification. Various processes or components may be omitted, substituted, or added as needed in the examples. Furthermore, some features described in the examples may be combined in other examples.
[0035] Example 1
[0036] In this Example 1, a refreshing composition based on plant essential oils is proposed, comprising the following components in parts by weight: 25 parts menthol, 12 parts borneol, 13 parts lime oil, 10 parts patchouli oil, 10 parts lavender oil, 10 parts basil, 9 parts geranium oil, 5 parts clove oil, and 5 parts eucalyptus oil.
[0037] The composition also includes a three-layer composite delivery system, a plant-derived emulsifier composite biphase system, and a protective and antioxidant protective layer;
[0038] The three-layer composite delivery system includes: an ion gel sustained-release base layer, which is formed by cross-linking natural polysaccharides with multivalent metal ions and has a gradient distribution of cross-linking degree from the surface to the interior;
[0039] The natural polysaccharides are selected from sodium alginate, chitosan and their combinations; the multivalent metal ions are selected from calcium ions, zinc ions and their combinations.
[0040] The crosslinking degree gradient distribution of the ionogel sustained-release base layer is as follows: surface crosslinking degree is 35%, and internal crosslinking degree is 75%.
[0041] The plant-derived emulsifier complex biphase system includes an aqueous phase and an oil phase, wherein the hydrophilic essential oil component is loaded in the aqueous phase and the hydrophobic essential oil component is loaded in the oil phase;
[0042] The plant-derived emulsifiers in the plant-derived emulsifier complex two-phase system are selected from saponins, lecithin, protein hydrolysates, sucrose fatty acid esters and combinations thereof.
[0043] The plant-derived emulsifier complex biphase system forms a secondary network structure, constituting a hierarchical slow-release system within a "network within a network";
[0044] Plant-derived light-shielding agents include anthocyanins and lycopene; plant-derived free radical scavengers include tea polyphenols and rosemary extract; plant-derived antioxidants include tocopherols and carotenoids.
[0045] The photoprotection and antioxidant protective layer includes a light shielding layer, a free radical scavenging layer, and an antioxidant layer. The light shielding layer contains plant-derived light shielding agents, the free radical scavenging layer contains plant-derived free radical scavengers, and the antioxidant layer contains plant-derived antioxidants.
[0046] The composition achieves a three-stage essential oil delivery mode: a rapid release phase (0-15 minutes) releasing 25±5% of the active ingredients, a sustained release phase (15 minutes-8 hours) releasing 50±5% of the active ingredients, and a deep release phase (8-24 hours) releasing 15±5% of the active ingredients.
[0047] Example 2
[0048] The difference between this embodiment and Embodiment 1 is that:
[0049] The invigorating composition comprises the following ingredients in parts by weight: 20 parts menthol, 10 parts borneol, 10 parts lime oil, 8 parts patchouli oil, 8 parts lavender oil, 8 parts basil, 7 parts geranium oil, 3 parts clove oil, and 3 parts eucalyptus oil.
[0050] Example 3
[0051] The difference between this embodiment and Embodiment 1 is that:
[0052] The invigorating composition comprises the following ingredients in parts by weight: 30 parts menthol, 15 parts borneol, 15 parts lime oil, 12 parts patchouli oil, 12 parts lavender oil, 12 parts basil, 11 parts geranium oil, 7 parts clove oil, and 7 parts eucalyptus oil.
[0053] Example 4
[0054] This embodiment presents a method for preparing a refreshing composition based on plant essential oils, comprising the following specific steps:
[0055] 1. Preparation of essential oil-based stimulating compositions
[0056] The essential oil invigorating composition consists of the following ingredients: menthol (L-menthol, purity ≥98%): 25 parts, melting point: 41-44℃, molecular weight: 156.27; borneol (natural borneol, purity ≥95%): 13 parts, melting point: 175-180℃, molecular weight: 152.23; lime oil (cold-pressed extract, d-limonene content ≥65%): 13 parts; patchouli oil (steam-distilled extract, patchouli alcohol content ≥30%). 10 parts; Lavender oil (steam distillation extract, linalool content ≥35%): 10 parts; Basil oil (steam distillation extract, linalool content ≥40%): 10 parts; Geranium oil (steam distillation extract, geraniol content ≥45%): 9 parts; Clove oil (steam distillation extract, eugenol content ≥80%): 5 parts; Eucalyptus oil (steam distillation extract, 1,8-cineole content ≥70%): 5 parts.
[0057] All components are pharmaceutical-grade essential oils, with the following volatility in descending order: menthol > eucalyptus leaf oil > lime oil > borneol > basil oil > lavender oil > geranium oil > clove oil > patchouli oil. The percentages above represent the mass percentage of each component in the final essential oil invigorating composition.
[0058] 2. Construction of the Iongel Sustained-Release Base Layer
[0059] Preparation of natural polysaccharide solution:
[0060] Sodium alginate: food grade, viscosity (1% aqueous solution, 25℃): 300-500 mPa·s, M / G ratio = 1.5-1.8, relative molecular weight: 80,000-120,000.
[0061] Chitosan: Food grade, degree of deacetylation ≥90%, relative molecular weight: 100,000-300,000, viscosity (1% acetic acid solution, 25℃): 200-800 mPa·s. Sodium alginate solution preparation and process parameter range:
[0062] Concentration range: can be adjusted within the range of 2.0-3.0%. Below 2.0%, the gel strength is insufficient, and above 3.0%, the solution viscosity is too high and difficult to handle.
[0063] Dissolution conditions: Accurately weigh 2.5±0.05g of sodium alginate (adjustable within the range of 2.0-3.0g) and slowly add it to 100ml of ultrapure deionized water with a resistivity ≥18MΩ·cm.
[0064] Stirring parameters: Use a mechanical stirrer (100-200 rpm) to stir for 4-5 hours at room temperature (20-25℃) to form a transparent and homogeneous solution.
[0065] Quality controls: The solution should be free of visible insoluble matter and have a clarity ≥95% (determined by spectrophotometry).
[0066] Preparation of polysaccharide-essential oil premix system:
[0067] Operating condition control:
[0068] Temperature control: The entire mixing process is carried out in a constant temperature environment of 25±1℃;
[0069] Humidity control: The relative humidity should be controlled at 40-50% to prevent moisture evaporation from changing the system concentration;
[0070] Anti-oxidation measures: Nitrogen gas is introduced into the operating environment to protect the essential oils from oxidation;
[0071] Adding essential oils: Preheat the essential oil refreshing composition prepared in step 1 to 25°C, and slowly add it to the mixed polysaccharide solution under stirring (300 rpm) at a ratio of 10% of the total mass of the polysaccharide solution (i.e., about 3g of essential oil composition).
[0072] Preliminary emulsification: Premix for 5 minutes using a low-speed shear mixer (2000 rpm) to form a coarse emulsion;
[0073] High shear homogenization: The crude emulsion was transferred to a high shear homogenizer and processed at 8000 rpm for 10 minutes under a first-stage pressure of 40 MPa and a second-stage pressure of 10 MPa to form a polysaccharide-essential oil premix with an average particle size of 2-5 μm.
[0074] Intermediate component testing: Take a small sample and use a laser particle size analyzer to determine the particle size distribution. The required particle size distribution is D90 < 10 μm and polydispersity index < 0.3. Simultaneously, observe the uniformity of essential oil droplet distribution under a microscope to ensure there is no obvious aggregation. Non-conforming products must be returned to the previous step for reprocessing.
[0075] Formation of ionic cross-linked networks:
[0076] Standard equipment: a double-layered glass reactor with a precision temperature control system (accuracy ±0.5℃).
[0077] Mixing device: Equipped with a variable speed mixer (20-500rpm) and a PTFE-coated impeller.
[0078] Dropping control: A micro-titer device is installed to precisely control the dropping speed.
[0079] Crosslinking solution preparation and parameter range:
[0080] Composition range of composite metal ion crosslinking solution:
[0081] Calcium chloride concentration: adjustable in the range of 1.5-2.5%. Below 1.5%, cross-linking is insufficient, and above 2.5%, surface cross-linking will be too fast.
[0082] Zinc chloride concentration: adjustable in the range of 0.3-0.7%. Adding zinc chloride improves network stability, but excessive amounts can increase toxicity.
[0083] Standard formulation: Dissolve 4±0.05g of analytical grade calcium chloride (purity ≥99%) and 1±0.05g of zinc chloride (purity ≥98%) in 200ml of deionized water;
[0084] Low-concentration crosslinking solution: The standard is to dilute the high-concentration crosslinking solution 4 times to prepare a mixed solution of 0.5% calcium chloride and 0.125% zinc chloride. Dilution range: The dilution ratio can be adjusted within the range of 3-5 times, which will affect the degree of surface crosslinking.
[0085] pH adjustment range: The pH of the crosslinking solution can be adjusted within the range of 5.5-7.0, with the standard being 6.0-6.5, using 0.1mol / L NaOH or HCl solution for adjustment.
[0086] Crosslinking process control parameter range:
[0087] Temperature range: 2-6℃ is acceptable, with 4±1℃ being optimal. Excessive temperature will cause irregular gel formation.
[0088] Stirring speed range: 100-200 rpm is acceptable, with 150 rpm being the standard. Too high a speed will cause droplet deformation.
[0089] Dropping rate range: 1-4 drops / second (approximately 0.3-1.0 ml / minute), standard is 2-3 drops / second, which affects particle shape uniformity;
[0090] Dropping height range: 3-8cm is acceptable, with 5cm being the standard. Too high a height will cause the droplets to deform, while too low a height will prevent them from forming a spherical shape.
[0091] Gradient crosslinking process parameter range:
[0092] Surface crosslinking time range: 10-20 minutes is acceptable, with a standard of 15±1 minutes; Low concentration range: 0.3-0.7% calcium chloride solution can be used for surface crosslinking;
[0093] Deep crosslinking time range: 20-40 minutes is acceptable, with a standard of 30±2 minutes; High concentration range: 1.5-2.5% calcium chloride solution can be used for deep crosslinking;
[0094] Crosslinking degree judgment standard: a compressive strength of 70-120kPa (at 50% deformation rate) is considered qualified, and the standard requires 80-100kPa; products that do not meet the standard need to extend the crosslinking time or adjust the crosslinking solution concentration and reprocess.
[0095] During the droplet addition of the polysaccharide solution to the metal ion solution, the droplet surface first contacts the metal ions, forming a transient gel film. Subsequently, the ions gradually penetrate and cross-link into the interior, forming a spherical structure. Precise control of the dropping rate and height ensures the uniformity of particle morphology, while the gradient cross-linking process prevents surface breakage.
[0096] The gradient crosslinking process employed results in a loose network (approximately 30-40% crosslinking degree) on the particle surface in a low-concentration crosslinking solution, while a tight network (approximately 70-80% crosslinking degree) forms inside in a high-concentration crosslinking solution. This gradient structure is generated by the diffusion effect of metal ions from the outside to the inside concentration gradient and is strengthened through a two-stage crosslinking process.
[0097] During the cross-linking process between polysaccharide chains, the irregular arrangement of molecular chains forms nanoscale pores. The combined use of sodium alginate and chitosan produces a synergistic effect: sodium alginate provides the main ionic cross-linking sites (carboxyl groups and Ca2+). 2+ / Zn 2+ (Combined), while chitosan enhances network stability through the electrostatic interaction between amino and carboxyl groups, while introducing additional physical spatial barriers to form a pore structure of a certain size.
[0098] The "egg-box model" formed by the ion-crosslinked network is the main source of mechanical strength, in which Ca... 2+ It forms a characteristic cross-linking region with the G segment of sodium alginate, while Zn 2+ It can simultaneously form coordination bonds with the M and G segments of sodium alginate, further enhancing the mechanical stability of the three-dimensional network. The high water content is generated by the numerous hydrogen bonds formed between the hydrophilic functional groups (hydroxyl and carboxyl groups) of the polysaccharide chain and water molecules.
[0099] Release process description: The outer layer with low cross-linking degree has a looser network structure and more free hydroxyl / amino functional groups, exhibiting a higher affinity for hydrophilic essential oil components (such as menthol and some water-soluble components of lime oil) and providing a faster release rate. Conversely, the inner layer with high cross-linking degree has a tighter hydrophobic microenvironment, exhibiting stronger encapsulation ability for hydrophobic essential oil components (such as borneol and patchouli oil), providing a slow and sustained release. This dual affinity is generated by the amphiphilic characteristics of the ionogel network structure, enabling selective controlled release of essential oil components with different polarities.
[0100] Through the aforementioned combination of multiple structures and control of the cross-linking process, the prepared ionogel base layer possesses both excellent biocompatibility and provides an ideal carrier structure for the effective loading and selective release of essential oil components. This precise regulation of the cross-linking gradient and microstructure is the key foundation for achieving the subsequent progressive release of essential oils.
[0101] 3. Construction of a plant-derived emulsifier composite two-phase system
[0102] Preparation of plant-derived emulsifier complex system:
[0103] Emulsifier selection criteria:
[0104] Saponins: Tea saponins, purity ≥95%, HLB value = 16-18, surface activity (CMC) = 0.05-0.08 mg / ml;
[0105] Lecithin: Soy lecithin, phosphatidylcholine content ≥80%, HLB value = 4-6, peroxide value ≤10 meq / kg;
[0106] Protein hydrolysate: soybean protein hydrolysate, average molecular weight 5,000-8,000 Da, peptide content ≥85%;
[0107] Sucrose fatty acid esters: sucrose stearate, purity ≥95%, HLB value = 14-16, melting point 55-60℃.
[0108] Preparation of oil phase emulsifier system:
[0109] Formula composition: saponins 0.8±0.02g, lecithin 1.2±0.02g and protein hydrolysate 1.0±0.02g;
[0110] Carrier oil: 20±0.5ml of medium-chain triglycerides with low acid value (≤0.5mgKOH / g) and high antioxidant properties (peroxide value ≤5meq / kg);
[0111] Operating conditions: Stir for 20 minutes using a homogenizer (2000 rpm) in a water bath at 50±1℃;
[0112] Quality control: Monitor the viscosity change of the system in real time; the final viscosity should reach 80-120 mPa·s (25℃).
[0113] Storage conditions: After preparation, store in a sealed container under nitrogen protection to avoid oxidation.
[0114] Preparation of aqueous emulsifier system:
[0115] Formula composition: 0.5±0.02g of sucrose fatty acid ester;
[0116] Solvent selection: Use 30±0.5ml of ultrapure deionized water with a resistivity ≥18MΩ·cm;
[0117] Operating conditions: Dissolve in a water bath at 40±1℃ and stir for 10 minutes using a magnetic stirrer (500 rpm);
[0118] Quality control: Visually inspect the clarity of the solution; there should be no suspended particles or precipitates.
[0119] Extraction and loading of hydrophilic components:
[0120] Target components: hydrophilic essential oil components (logP<3), mainly including menthol (logP=2.74), geraniol in some lime oil (logP=2.58), and the water-soluble fraction in eucalyptus leaf oil;
[0121] Extraction method: Extract with a 40% ethanol-water mixture at 15°C with shaking for 30 minutes (150 rpm);
[0122] Loading process: The extracted hydrophilic component is slowly added dropwise (1 ml / min) to the aqueous emulsifier system at a ratio of 5% (approximately 1.5 g) of the total mass of the aqueous phase;
[0123] Homogenization conditions: Pulse processing for 10 minutes using an ultrasonic processor (300W power, 20kHz frequency) (5 seconds of operation, 2 seconds of rest);
[0124] Quality control: The turbidity of the system after loading is ≤10 NTU, and the particle size distribution is 100-200 nm (determined by dynamic light scattering method).
[0125] Extraction and loading of hydrophobic components:
[0126] Target components: hydrophobic essential oil components (logP≥3), mainly including oil-soluble components in borneol (logP=3.04), patchouli oil (logP=4.5-5.5), lavender oil (logP=3.5-4.5), basil oil (logP=3.2-4.2), geranium oil (logP=3.8-4.8), and clove oil (logP=3.3-4.3);
[0127] Extraction method: Extract with n-hexane at 15°C with shaking for 30 minutes (150 rpm);
[0128] Loading process: The extracted hydrophobic component is slowly added to the oil phase emulsifier system at a ratio of 7.5% (approximately 1.5g) of the total mass of the oil phase;
[0129] Homogenization conditions: Pulse processing for 10 minutes using an ultrasonic processor (300W power, 20kHz frequency) (5 seconds of operation, 2 seconds of rest);
[0130] Quality control: After loading, the oil phase transparency is ≥90%, with no obvious sedimentation or stratification.
[0131] Formation of the biphasic microemulsion system:
[0132] Microemulsion preparation equipment:
[0133] High-pressure homogenizer: maximum working pressure 100MPa, adjustable flow rate 0.5-5L / h;
[0134] Ultrasonic processor: frequency 20-25kHz, power adjustable (0-600W);
[0135] Temperature control system: accuracy ±0.5℃, operating temperature range 0-80℃.
[0136] Preparation before emulsification:
[0137] Oil-water phase temperature equilibrium: Adjust the oil phase and water phase to 30±2℃ respectively;
[0138] The ratio is determined as follows: oil phase:water phase = 1:1.5 (20ml oil phase to 30ml water phase);
[0139] Surfactant concentration: The total surfactant concentration should be controlled at 5-7% of the total mass of the system.
[0140] Primary emulsification:
[0141] Addition method: Use a constant flow pump to slowly add the oil phase system to the continuously stirred (500 rpm) aqueous phase system at a rate of 2 ml / min;
[0142] Temperature conditions: Maintained at 30±2℃ throughout the process;
[0143] Colostrum formation: Premix for 5 minutes using a low-speed homogenizer (3000 rpm) to form a coarse emulsion.
[0144] High-efficiency emulsification treatment:
[0145] High-pressure homogenization: The crude emulsion is passed through a high-pressure homogenizer, with a first-stage pressure of 60 MPa and a second-stage pressure of 15 MPa, and the cycle is repeated 3 times.
[0146] Alternating ultrasonic-homogenization treatment: The emulsion after high-pressure homogenization is ultrasonically treated (300W, 2 minutes) and then immediately subjected to high-speed shear homogenization (12000rpm, 1 minute). This process is repeated 3 times.
[0147] Degassing treatment: Degas under vacuum (-0.08MPa) at 25℃ for 10 minutes to remove air bubbles introduced during the preparation process.
[0148] Construction of multi-layered gel networks:
[0149] Equipment and material preparation:
[0150] Temperature-controlled reactor: Double-layered glass reactor, equipped with a precision temperature control system (±0.1℃) and programmable heating and cooling control;
[0151] Ion gel pretreatment: The ion gel base layer prepared in step 2 is vacuum dried at 30°C to a water content of 50-60% (wet basis) to improve the adsorption capacity;
[0152] Crosslinking agent preparation: Prepare a 0.1% phosphate buffer solution (pH 7.2) using analytical grade glutaraldehyde (purity ≥ 25%).
[0153] Reaction vessel: A sealed glass reactor purged with nitrogen to avoid oxidation reactions during the crosslinking process.
[0154] Carrier-microemulsion integration process:
[0155] Soaking process: The treated ion gel sustained-release base layer was slowly added to the microemulsion system at a ratio of ion gel:microemulsion system = 1:3 (w / v);
[0156] Penetration conditions: Use a low-speed rotary mixer (30 rpm) to gently stir, ensuring that the gel particles fully contact the microemulsion without damaging its structure;
[0157] Vacuum-assisted permeation: A slight negative pressure (-0.02 MPa) is applied within the first 30 minutes to promote the migration of microemulsion components into the gel.
[0158] Secondary network cross-linking process:
[0159] Crosslinking agent addition: Add 0.1% glutaraldehyde buffer dropwise to the system using a micro-injection pump (0.5 ml / min), at a volume of 5% of the total system volume;
[0160] Crosslinking conditions: Stir gently for 4 hours at 25±1℃ using a low-speed stirrer (50 rpm);
[0161] Crosslinking degree monitoring: Samples are taken every hour, and the change in thermal stability of the gel is determined by differential scanning calorimetry (DSC). The gelation temperature should be gradually increased.
[0162] Endpoint determination: The crosslinking reaction reaches its endpoint when the gel strength reaches 150-180% of the initial strength.
[0163] Through the above steps, the ionogel sustained-release base layer and the plant-derived emulsifier composite two-phase system are integrated into a single entity, forming a composite carrier system with progressive release function. This step is a key connecting point in the process flow, organically combining the products of the first two steps. Its working mechanism and synergistic effects are as follows:
[0164] Basic structure and function of a two-phase delivery system:
[0165] Structural features: The system consists of an ion gel matrix and microemulsion droplets dispersed within it, forming a "composite carrier within a composite carrier" structure;
[0166] Structural parameters: The average droplet size of the microemulsion is 50-200 nm, with uniform distribution and a polydispersity index <0.3. The distribution density in the gel network is 10. 5 -10 6 pcs / mm 3 ;
[0167] Working principle: This system achieves independent loading and synergistic release of different hydrophilic essential oil components through a "phase separation but functional synergy" approach.
[0168] Component distribution: Hydrophilic essential oil components (logP<3) are mainly distributed in the hydrophilic regions of aqueous microemulsion droplets and gel network, while hydrophobic components (logP≥3) are distributed in the hydrophobic regions of oil microemulsion droplets and gel network.
[0169] The stabilization mechanism of microemulsion systems:
[0170] Sources of interfacial stability: Plant-derived emulsifiers (saponins, lecithin, and protein hydrolysates) stabilize microemulsion droplets by forming a strong interfacial film;
[0171] Microstructure plays a role: the macromolecular structure of saponins provides steric hindrance, lecithin forms a dense phospholipid bilayer, and protein hydrolysates enhance interfacial elasticity through multi-point adsorption.
[0172] Thermodynamic stability: By optimizing the HLB value (oil phase HLB 8.5-9.5, aqueous phase HLB 14-16), the microemulsion system reaches a thermodynamically stable state, avoiding phase separation;
[0173] Formation and function of dual-network cross-linked structures:
[0174] Network structure: The system consists of two levels: a primary network (formed by ionic cross-linking) and a secondary network (formed by glutaraldehyde cross-linking);
[0175] Network parameters: average pore size of the main network is 10-30 nm, average pore size of the secondary network is 5-15 nm, cross-linking degree of the main network is 30-80% (gradient distribution), and cross-linking degree of the secondary network is 40-60%.
[0176] Formation process: When glutaraldehyde is added to the system, its dialdehyde groups react with the amino groups in chitosan and protein hydrolysates to form covalent crosslinks.
[0177] Functional combination: The main network provides the overall framework and basic mechanical properties, while the secondary network forms an additional encapsulation layer around the microemulsion droplets to prevent microemulsion droplet aggregation and content leakage.
[0178] The process of temperature gradient permeation:
[0179] During the temperature rise phase (25℃→40℃): the gel network expands, the pore size increases, promoting the penetration of microemulsion droplets into the gel interior; at the same time, the size of the microemulsion droplets decreases slightly, which is beneficial for their migration.
[0180] Precise temperature parameter control: heating rate 0.25±0.02℃ / min, temperature uniformity ±0.5℃ (using multi-point temperature probe monitoring);
[0181] Isothermal phase (40℃ for 2 hours): Maintain the network open to ensure that the microemulsion droplets fully penetrate and are evenly distributed;
[0182] During the temperature reduction phase (40℃→25℃): the network shrinks, the pore size decreases, the position of the microemulsion droplets is fixed, and a stable composite structure is formed;
[0183] Scientific basis: This process utilizes the thermosensitive properties of sodium alginate gel and the rheological properties of microemulsion systems to achieve precise distribution of substances in three-dimensional space through temperature control.
[0184] Permeation process monitoring: The migration and distribution of microemulsion droplets in the gel network were monitored in real time using a combination of fluorescence labeling and laser confocal microscopy;
[0185] How to implement the progressive release function:
[0186] Three-stage release mode: The system forms a three-stage essential oil delivery process of "rapid release - continuous release - deep release";
[0187] Release kinetic parameters: Phase 1 (0-15 minutes) release 25.3±1.2%, Phase 2 (15 minutes-8 hours) release 59.9±2.4%, Phase 3 (8-24 hours) release 14.8±1.5%;
[0188] Phase 1 (rapid release): The outer microemulsion droplets rupture and the surface gel network releases, providing an immediate refreshing effect (0-15 minutes);
[0189] Second stage (continuous release): The contents are slowly released from the middle layer microemulsion droplets, and the diffusion rate is regulated by the secondary network to maintain a long-lasting effect (15 minutes to 8 hours);
[0190] The third stage (deep release): The highly cross-linked inner layer slowly degrades, releasing the deeply encapsulated essential oil components and extending the total effective time (8-24 hours);
[0191] This multi-synergistic composite carrier system achieves efficient loading and controllable release of different hydrophilic essential oil components by precisely controlling the distribution and release kinetics of different components in the system, providing key support for the long-term stable effect of essential oil stimulating compositions.
[0192] 4. Addition of photoprotective and antioxidant protective layers
[0193] Preparation of plant-derived light-shielding agents:
[0194] Raw material selection criteria:
[0195] Requirements for red fruits: organically grown ripe tomatoes (lycopene content ≥10mg / 100g) and strawberries (anthocyanin content ≥30mg / 100g);
[0196] Auxiliary reagents: food-grade ethanol (purity ≥ 95%) and ultrapure water (resistivity ≥ 18 MΩ·cm);
[0197] Extraction carrier: HP-20 macroporous adsorption resin (average pore size 45-55nm, specific surface area 500-600m² / g).
[0198] Raw material pretreatment:
[0199] Fruit washing: Wash the surface of the fruit with a 0.1% citric acid solution to remove pesticide residues and impurities;
[0200] Crushing process: 50±1g each of fresh tomatoes and strawberries are crushed into a homogeneous slurry (particle size ≤1mm) under nitrogen protection;
[0201] Antioxidant treatment: Immediately add 0.1% ascorbic acid solution to prevent the oxidation of phenolic compounds.
[0202] Extraction of active ingredients:
[0203] Solvent system: Use 200±5ml of ethanol / water mixed solution (volume ratio 7:3, pH adjusted to 4.0-4.5);
[0204] Extraction conditions: Extract for 2 hours in a water bath at 50±1℃ using a magnetic stirrer (300 rpm);
[0205] Solid-liquid separation: Filter using a 200-mesh filter cloth to separate the extract and residue;
[0206] Secondary extraction: The filter residue is extracted again under the same conditions to improve the recovery rate of effective components.
[0207] Extract concentration and purification:
[0208] Concentration parameters: Concentrate to 1 / 5 of the original volume using a rotary evaporator at 45±2℃ and -0.08MPa.
[0209] Lycopene purification:
[0210] Supercritical CO2 extraction was used, with the following operating parameters: temperature 40±1℃, pressure 25±0.5MPa, and CO2 flow rate 8-10L / min.
[0211] Using 10% ethanol as a co-solvent improves the solubility of lycopene;
[0212] Segmented collection: Collect in three segments according to the pressure gradient (23-27MPa), and take the middle segment product (purity ≥90%).
[0213] Anthocyanin purification:
[0214] Pretreatment: Adjust the pH of the concentrate to 3.0±0.2, which is beneficial for anthocyanin stability;
[0215] Macroporous resin column chromatography was used: HP-20 resin (column bed volume 100 ml) was used, and the flow rate was controlled at 2 BV / h.
[0216] Elution conditions: Gradient elution was performed using an ethanol / water / citric acid system (70:29.5:0.5);
[0217] Purified product specifications: anthocyanin content ≥95%, total phenol content ≥98%.
[0218] Light shielding agent quality control:
[0219] Active ingredient detection: Lycopene content ≥95% and anthocyanin content ≥90% were determined using high performance liquid chromatography (HPLC).
[0220] UV shielding efficiency: In the 280-400nm wavelength range, the average shielding efficiency of a 1% solution is ≥90%;
[0221] Visible light shielding properties: In the 400-700nm wavelength range, the average shielding efficiency of a 1% solution is ≥30%;
[0222] Stability test: After storage at 25℃ in the dark for 30 days, the loss rate of active ingredients is ≤5%.
[0223] Preparation of plant-derived free radical scavengers:
[0224] Raw material pretreatment:
[0225] Drying treatment: The raw material is dried at 45±2℃ until the moisture content is ≤5%;
[0226] Safety Precautions: The drying process should be carried out in a well-ventilated environment to prevent the accumulation of volatile substances; the drying temperature should not exceed 50℃ to avoid oxidation and deterioration of polyphenols.
[0227] Grinding process: Use a low-temperature grinder (pre-cooled at -20℃) to grind the raw materials into 60-80 mesh fine powder;
[0228] Safety precautions: Low temperature environment can reduce the oxidation and volatilization of active ingredients during the pulverization process; operators should wear dust masks to avoid inhaling plant dust.
[0229] Screening: Use an 80-mesh standard sieve to screen the particles to ensure uniform particle size;
[0230] Chemical compatibility: The screen material should be stainless steel or nylon, avoiding metal materials that react with plant polyphenols.
[0231] Extraction of polyphenolic compounds:
[0232] Solvent system selection: Use 70% (v / v) food-grade ethanol aqueous solution, and adjust the pH value to 5.5-6.0;
[0233] Safety precautions: Ethanol is flammable. The operating area should be kept away from open flames, equipped with fire extinguishers, and ensure good ventilation.
[0234] Solid-liquid ratio: The mass ratio of raw materials to solvent is 1:10 (w / v), that is, 15±0.2g of tea leaves and rosemary are added to 300ml of solvent;
[0235] Ultrasonic-assisted extraction: Using an ultrasonic extraction device, frequency 40kHz, power 300W, pulse mode (working for 10 seconds, stopping for 2 seconds);
[0236] Safety precautions: Ultrasonic equipment should be equipped with sound insulation measures during operation, and operators should wear earplugs to avoid prolonged exposure to noisy environments;
[0237] Equipment safety: The ultrasonic extraction equipment should be placed on a stable platform to prevent vibration from causing the solution to splash out;
[0238] Extraction conditions: Extract at room temperature (22±2℃) for 30 minutes, stirring every 10 minutes to ensure uniform contact;
[0239] Secondary extraction: The residue is extracted again under the same conditions, and the two extracts are combined;
[0240] Chemical compatibility: During the extraction process, avoid using metal containers and tools such as iron and copper to prevent metal ions from catalyzing the oxidation of polyphenols. Containers made of glass, ceramic or specific plastic materials should be preferred.
[0241] Extract purification and concentration:
[0242] Solid-liquid separation: 0.45μm membrane filtration is used to remove insoluble substances;
[0243] Degreasing treatment: Extract twice with an equal volume of n-hexane to remove fat-soluble interfering substances;
[0244] Safety warning: Hexane is flammable and has some toxicity. Handling must be carried out in a fume hood, away from ignition sources, and operators should wear nitrile gloves and safety goggles.
[0245] Waste liquid treatment: Used n-hexane should be collected in a special container and treated as organic solvent waste liquid. It must not be dumped at will.
[0246] Preparation of plant-derived antioxidants:
[0247] Raw material selection criteria:
[0248] Vegetable oil: Wheat germ oil (virgin cold-pressed, peroxide value ≤3 meq / kg, tocopherol content ≥200mg / 100g).
[0249] Lecithin: Non-GMO soybean lecithin (phosphatidylcholine content ≥90%, peroxide value ≤5 meq / kg).
[0250] Carrots: Organically grown red carrots (β-carotene content ≥8mg / 100g).
[0251] Auxiliary ingredients: Natural vitamin E (d-α-tocopherol, purity ≥90%), rosemary extract (containing ≥5% rosmarinicol).
[0252] Preparation of tocopherol enrichment system:
[0253] Wheat germ oil treatment: Tocopherols were enriched in wheat germ oil using molecular distillation technology (temperature 180-200℃, pressure 1-5Pa).
[0254] Enrichment effect test: The tocopherol content should reach ≥400mg / 100g (determined by HPLC).
[0255] Antioxidant enhancement treatment: 1g of natural vitamin E and 0.5g of rosemary extract are added to every 100ml of enriched oil to improve antioxidant capacity.
[0256] Liposome carrier preparation:
[0257] Formula composition: 5±0.1ml of enriched wheat germ oil and 1.5±0.05g of lecithin.
[0258] Homogenization conditions: Process for 15 minutes in a water bath at 50±2℃ using a high-shear homogenizer (10000rpm).
[0259] Particle size control: Liposomes with an average particle size of 100-200 nm were obtained by high-pressure homogenization (30 MPa) three times.
[0260] Stability test: After standing at 25℃ for 24 hours, there was no obvious stratification or precipitation.
[0261] Carotenoid extraction and enrichment:
[0262] Raw material processing: Wash, peel, and chop the carrots, dry them at 60±2℃ until the moisture content is ≤10%, and then grind them to 60-80 mesh.
[0263] Extraction carrier: Medium-chain triglycerides (MCT) are selected as the extraction solvent, which has better antioxidant properties than ordinary vegetable oils.
[0264] Extraction process: Add 30±0.5g of carrot powder to 50±1ml of MCT oil and heat in a water bath at 60±2℃ for 2 hours under nitrogen protection.
[0265] Extraction enhancement measures: Sonication (40kHz) for 5 minutes every 30 minutes to enhance the release of carotenoids.
[0266] Solid-liquid separation: Use a 100-mesh filter cloth to filter and remove carrot residue.
[0267] Clarification: Use a centrifuge (5000 rpm, 10 minutes) to further remove suspended solids.
[0268] Antioxidant system integration and stabilization:
[0269] Two systems were mixed: the prepared liposomes were mixed with carotenoid oil at a ratio of 2:3 (v / v).
[0270] Mixing conditions: Mix for 15 minutes at 40±2℃ using a low-speed mixer (200 rpm).
[0271] Homogenization: Use an ultrasonic processor (300W, 20kHz) to process intermittently for 5 minutes (10 seconds on, 5 seconds off).
[0272] Antioxidant synergist addition: Add 0.5g ascorbyl palmitate to every 100ml of mixture to enhance the antioxidant synergistic effect.
[0273] Functional layer structure design principles:
[0274] Multilayer structure principle: It adopts layer-by-layer self-assembly technology (LbL) and is constructed according to the sequence of "light shielding layer - free radical scavenging layer - antioxidant layer".
[0275] Functional complementarity: The three-layer structure forms a complete light protection chain, targeting light incident blocking, free radical capture, and oxidation reaction termination respectively.
[0276] Biocompatibility considerations: All components are plant-derived, ensuring product safety and environmental friendliness.
[0277] Preparation of outer light-shielding gel:
[0278] Carrier selection: Food-grade alginate (viscosity 300-500 mPa·s, M / G ratio = 1.5-1.7) was used as the matrix for the light shielding layer.
[0279] Formula composition: Accurately weigh 0.5±0.01g of alginate and dissolve it in 50±1ml of ultrapure water.
[0280] Dissolution process: First, use 80℃ hot water to quickly stir and dissolve for 5 minutes, then cool down to 40℃ and continue stirring for 15 minutes.
[0281] Light shielding agent integration: Add the light shielding agent prepared in step 1) to the alginate solution at a ratio of 5% (2.5 ml) of the total system.
[0282] Homogenization: Use a low-shear homogenizer (3000 rpm) for 10 minutes to ensure uniform dispersion.
[0283] Stabilization treatment: Add 0.2% xanthan gum as a stabilizer to prevent component separation.
[0284] Composite carrier integration process (layer-by-layer encapsulation method):
[0285] Equipment preparation: Use a glass reactor with precise temperature control (±0.5℃) and variable speed stirring (10-500rpm).
[0286] Operating environment: constant temperature of 25±1℃, relative humidity controlled at 45-55%.
[0287] Addition method: Slowly add the composite carrier system prepared in step 4.3 into the light-shielding gel at a rate of 2 ml / min.
[0288] Ratio control: The volume ratio of composite carrier system to light-shielding gel is 1:2 (i.e., 30 ml of composite carrier system is added to 60 ml of light-shielding gel).
[0289] Mixing parameters: Use an impeller mixer at 80 rpm and gently mix for 30 minutes.
[0290] Uniformity test: Samples were taken for microscopic observation to confirm that the composite carrier was uniformly dispersed in the light-shielding gel.
[0291] Static stability: After standing at room temperature for 1 hour, a primary composite system is formed.
[0292] Construction of the intermediate protective layer:
[0293] Spraying equipment: Use micron-level sprayers (spray particle size 5-10μm) to ensure uniform coverage.
[0294] Spray parameters: distance 10cm, spray pressure 0.2MPa, uniform rotation spray.
[0295] Addition amount control: Spray the plant-derived free radical scavenger prepared in step 2 evenly onto the surface of the primary composite system at a dosage of 5 ml / 100 cm².
[0296] Spraying technology: Employs multi-point, multi-angle, and multi-layer spraying methods to ensure uniform coverage.
[0297] Drying conditions: 25±2℃, relative humidity 40±5%, dry for 15 minutes under ventilation.
[0298] Layer thickness control: The thickness of the intermediate protective layer is controlled at 100-150μm (detected using a laser confocal microscope).
[0299] Construction of the outermost antioxidant defense line:
[0300] Coating tool: A precision coater is used to control the coating thickness within the range of 50-200μm.
[0301] Coating technology: The "wet-to-wet" coating method is used, which is carried out when the intermediate layer is not completely dry, to enhance the interlayer bonding force.
[0302] Antioxidant addition: The plant-derived antioxidant mixture prepared in step 3) is uniformly coated on the surface of the intermediate protective layer at a dosage of 3 ml / 100 cm².
[0303] Coating parameters: Coating speed 5cm / s, coating pressure 200g / cm², to ensure coating uniformity.
[0304] Thickness control: The thickness of the outermost anti-oxidation defense layer is controlled at 80-120μm (detected using a laser confocal microscope).
[0305] Multi-layer structure stabilization process:
[0306] Alternating drying-humidification cycle treatment:
[0307] First stage: Dry at 25±1℃ and 30±5% relative humidity for 30±2 minutes.
[0308] Second stage: Transfer to a humid environment with a relative humidity of 60±5% for 60±5 minutes to equilibrate.
[0309] Number of cycles: Repeat the above drying-wetting cycle twice.
[0310] Stabilization mechanism: The drying process promotes the entanglement of polymer chains, the wetting process promotes the formation of intermolecular hydrogen bonds, and the alternating treatment enhances the interlayer bonding force.
[0311] Quality control: After each cycle, samples are taken for structural stability testing, including abrasion resistance, water resistance and interlayer bonding strength.
[0312] Multi-layer structure quality evaluation:
[0313] Structural integrity: Scanning electron microscopy revealed that the interfaces of each layer were clear and tightly bonded, with no obvious defects.
[0314] Functional layer thickness: outer layer 80-120μm, middle layer 100-150μm, total thickness controlled at 300-400μm.
[0315] Mechanical stability: Under a deformation rate of 50%, the structural integrity retention rate is ≥95%.
[0316] Optical shielding efficiency: Average shielding rate ≥85% in the wavelength range of 280-700nm.
[0317] Antioxidant capacity: Total antioxidant capacity ≥5000μmol TE / 100g, duration ≥24h.
[0318] Through the above steps, the composite carrier system prepared in step 3 is combined with photoprotective and antioxidant components to form a three-layer photoprotective and antioxidant synergistic protective structure, completing the construction of the entire delivery system. This step is the final functional layer addition step in the process flow, ensuring the stability of the product in complex environments. Its mechanism of action and synergistic effects are as follows:
[0319] Overall protection strategy and working principle:
[0320] Protection method: Adopt a triple protection strategy of "blocking the light source - clearing free radicals - terminating the oxidation chain".
[0321] The protective layers consist of an outer light shielding layer, a middle free radical scavenging layer, and an inner antioxidant defense layer.
[0322] Overall thickness: The total thickness of the three-layer structure is 300-400μm, with the outer layer at 80-120μm, the middle layer at 100-150μm, and the inner layer at 80-120μm.
[0323] Working process: The three layers work together to form a complete photo-oxidation defense system, preventing the active components of essential oils from being degraded and deteriorated due to light exposure.
[0324] Protection efficiency test: The average shielding efficiency in the wavelength range of 280-700nm was measured using a UV-Vis spectrophotometer and was ≥85%.
[0325] The working process of the optical shielding layer:
[0326] Shielding methods: Anthocyanins and lycopene absorb ultraviolet and visible light in different ways.
[0327] Shielding parameters: Anthocyanins have an average shielding rate of ≥90% in the 280-350nm band, and lycopene has an average shielding rate of ≥70% in the 400-550nm band.
[0328] Molecular interaction process: The conjugated double bond system of anthocyanins can effectively absorb UVB and UVA radiation in the range of 280-350nm; the long-chain conjugated polyene structure of lycopene mainly absorbs visible blue and green light in the range of 400-550nm.
[0329] Synergistic effect: The absorption spectra of the two pigments are complementary, jointly covering the spectral range of 280-550nm, with a shielding rate of over 85%.
[0330] Carrier function: Alginate not only serves as a carrier for pigments, but its sulfate groups also scatter some ultraviolet light.
[0331] Spectral characteristics determination: The absorption spectrum and transmittance of the shielding layer in the range of 200-800 nm were determined using a UV-Vis spectrophotometer.
[0332] The working process of the free radical scavenging layer:
[0333] Scavenging methods: Polyphenolic compounds neutralize free radicals through hydrogen donation and electron transfer;
[0334] Scavenging capacity parameters: DPPH radical scavenging capacity IC50 value ≤ 0.05 mg / ml, ABTS radical scavenging capacity ≥ 2000 μmol Trolox equivalent / g;
[0335] Molecular interaction process: Catechins in tea polyphenols neutralize hydroxyl radicals and superoxide anion radicals by donating hydrogen through phenolic hydroxyl groups; the ortho- and oxalic acid structures of rosmarinic acid and oxalic acid form stable semiquinone radicals, terminating the free radical chain reaction.
[0336] Synergistic effect: Different polyphenol components form a broad-spectrum scavenging effect against different types of free radicals.
[0337] Rapid effect: The free radical scavenging reaction is completed in microseconds, and it can quickly respond to free radicals generated by light.
[0338] How the antioxidant defense works:
[0339] Antioxidant methods: Block the chain reaction of lipid peroxidation and protect the unsaturated components in essential oils;
[0340] Antioxidant capacity parameters: Oxygen radical scavenging capacity (ORAC) ≥ 3000 μmol TE / 100g, peroxide value ≤ 5 meq / kg;
[0341] Molecular interaction process: The chromium-filled ring structure of tocopherol can provide hydrogen and stabilize peroxy free radicals; the conjugated polyene structure of carotenoids can directly quench singlet oxygen; ascorbate palmitate maintains the long-term effectiveness of the antioxidant system by regenerating oxidized tocopherol.
[0342] Location and distribution: Lipid-soluble antioxidants preferentially distribute at the oil-water interface and around essential oil molecules, forming directional protection;
[0343] Long-lasting effect: Antioxidants come into direct contact with essential oil components, providing continuous protection; the antioxidant capacity decreases by ≤10% during the usage period.
[0344] Active ingredient content: Tocopherol content ≥15mg / ml (determined by HPLC), β-carotene content ≥5mg / ml (determined by spectrophotometry).
[0345] The stabilization process of multilayer structures:
[0346] Interlayer bonding method: The "drying shrinkage-moistening expansion" cycle produced by alternating drying-moistening treatment;
[0347] Processing parameters: Drying stage (25±1℃, relative humidity 30±5%, 30±2 minutes), wetting stage (25±1℃, relative humidity 60±5%, 60±5 minutes), cycle 2 times;
[0348] Molecular bonding process: The drying stage promotes physical entanglement and local crystallization between molecular chains; the wetting stage promotes hydrogen bond formation and functional group rearrangement. The two processes alternate to enhance interlayer bonding forces.
[0349] Three-dimensional structural stability: By controlling the thickness ratio of each layer (outer layer:middle layer:inner layer = 1:1.5:1), the mechanical stability and functional synergy of the overall structure were optimized;
[0350] Permeation barrier effect: Selective material permeation barriers are formed between the functional layers, allowing essential oil molecules to be released slowly while blocking the penetration of oxygen and ultraviolet light.
[0351] 5. Final product molding and packaging
[0352] After completing the above four process steps, the product undergoes final shaping and packaging. This is the final step in the entire process, transforming the semi-finished product prepared in the previous steps into a usable final product. The specific process is as follows:
[0353] Product maturation and stabilization:
[0354] Stabilization environment control:
[0355] Temperature conditions: The three-layer composite system prepared in step 4 of the process flow is placed in a precision constant temperature refrigeration device at 4±0.5℃;
[0356] Humidity control: Maintain relative humidity at 60±5% to prevent the product from drying out excessively;
[0357] Light protection: A completely light-protected environment to prevent degradation of photosensitive components;
[0358] Stabilization time: 12 ± 0.5 hours to ensure full structural stability and full integration of functional components.
[0359] Maturity testing and evaluation:
[0360] Structural stability test: Compression resilience ≥90%, indicating that the internal network structure has been fully formed;
[0361] Component migration evaluation: Interlayer component migration rate ≤5% indicates that each functional layer has been effectively isolated;
[0362] Release pre-test: The initial release rate of 20-30% in the first 1 hour indicates that the controlled release function is normal;
[0363] Quality uniformity evaluation: Random sampling was used to determine the content of active ingredients, and the relative standard deviation (RSD) within the batch was ≤5%.
[0364] Product cutting and shaping (using the product stabilized in step 1):
[0365] Molding equipment and environment:
[0366] Equipment selection: Use precision CNC cutting equipment with a cutting accuracy of ±0.1mm.
[0367] Environmental conditions: Conducted in a Class 100 cleanroom (particle count ≤ 100 particles / cubic foot, particle size ≥ 0.5 μm).
[0368] Temperature and humidity control: Temperature 20±2℃, relative humidity 50±5% to prevent material deformation during cutting.
[0369] Molding parameters and specifications:
[0370] Patch products: circular patches with a diameter of 2-5cm (±0.2mm) and a thickness of 2-3mm (±0.1mm);
[0371] Microparticle type products: square patches with a side length of 1-3cm (±0.2mm) and a thickness of 2-3mm (±0.1mm);
[0372] Granular products: Spherical granules with a diameter of 2-5mm (±0.1mm), used for filling capsules or mixing with other carriers;
[0373] Cutting process: Ultrasonic vibration cutting technology is used to produce a smooth, burr-free cut surface, preventing damage to the functional layer.
[0374] Packaging process:
[0375] Packaging method: Surface mount products use heat sealing technology (temperature 180±5℃, pressure 0.5±0.05MPa, time 2±0.2s);
[0376] Glass bottle products: Tamper-proof aluminum caps are used for sealing, with torque controlled at 15±1 N·m;
[0377] Nitrogen purging: The air inside the container is purged with nitrogen before packaging, with residual oxygen content ≤2%;
[0378] Sterility testing: Samples are randomly selected from each batch for sterility testing, with a pass rate of 100%.
[0379] Experimental verification and test data
[0380] According to the technical solution of the present invention, three of the most innovative technical effects were selected for detailed experimental verification to demonstrate the technical advantages of the present invention. These three technical effects are: the influence of the multi-layer photoprotective structure on the stability of essential oils, the improvement of essential oil component loading efficiency by the separation and loading technology based on hydrophilicity differences, and the precise control of the essential oil release process by the multi-layer gel network.
[0381] Experiment 1: The effect of multi-layered photoprotective structure on the stability of essential oils
[0382] Experimental Objective
[0383] The protective effect of the multilayer photoprotection and antioxidant synergistic structure of the present invention on the stability of essential oil components under light conditions was verified.
[0384] Experimental materials
[0385] The complete three-layer structure product of this invention (sample A); a product containing only an ion gel sustained-release base layer and a microemulsion system, without a photoprotective layer (sample B); a commercially available essential oil patch product (sample C); a simulated sunlight irradiation device (adjustable light intensity, containing 10% UV); a gas chromatograph (equipped with an FID detector); standards: menthol, borneol, limonene (the main component of lime oil), patchouli alcohol (the main component of patchouli oil); internal standard: heptadecane.
[0386] Experimental steps
[0387] Sample preparation:
[0388] A complete three-layer structure product (sample A) was prepared according to Example 4; a product without a light-protective layer (sample B) was prepared according to Example 4; commercially available essential oil patch products (sample C) were purchased; 15 of each sample were prepared and divided into 5 groups for testing at different time points.
[0389] Lighting processing:
[0390] Three samples were placed simultaneously under a simulated sunlight irradiation device; the light intensity was set to 5000±100 lx, including 10% UV; the temperature was controlled at 25±1℃ and the relative humidity at 60±5%; the irradiation times were 0h, 2h, 4h, 6h and 8h respectively.
[0391] Sample extraction:
[0392] Three samples of each type were taken at each time point; 500 mg of sample was accurately weighed and 5 ml of hexane-ethanol mixed solvent (4:1, v / v) was added; the sample was extracted by sonication for 30 minutes and centrifuged (10000 rpm, 10 minutes) to collect the supernatant; 100 μg of heptadecane was added to the supernatant as an internal standard.
[0393] GC analysis conditions:
[0394] Chromatographic column: HP-5MS capillary column (30m×0.25mm×0.25μm); Carrier gas: high-purity helium, flow rate 1.0ml / min; Injector temperature: 250℃, split ratio 10:1; Column temperature: initial temperature 60℃ held for 2 minutes, increased to 180℃ at 5℃ / min, then increased to 250℃ at 10℃ / min held for 5 minutes; Detector: FID, temperature 280℃; Injection volume: 1μl.
[0395] Data processing:
[0396] Calculate the retention rate of each major essential oil component: Retention rate (%) = (Component content after light exposure / Initial component content) × 100%; Calculate the mean and standard deviation; Use one-way ANOVA to compare the differences between different samples, P < 0.05 indicates that the difference is statistically significant.
[0397] Experimental results
[0398] Table 1. Retention rate (%) of total essential oil components in three samples under different light exposure times
[0399]
[0400] Table 2. Retention rate (%) of different essential oil components after 8 hours of light exposure
[0401]
[0402] Figure 1The curves showing the changes in the retention rate of total essential oil components in three samples under different light exposure times are presented.
[0403] Results Analysis
[0404] Experimental results show that the product of this invention (sample A) retained as much as 85.7% of the total essential oil components after 8 hours of light exposure, while the retention rates of the product without a light-protective layer (sample B) and the commercially available product (sample C) were only 32.1% and 31.2%, respectively. This fully demonstrates the effectiveness of the multi-layered photoprotective and antioxidant synergistic structure. Specifically, the light-shielding layer formed by anthocyanins and lycopene effectively absorbs UV light, the free radical scavenging layer composed of tea polyphenols and rosemary extract promptly removes free radicals generated by light exposure, and the antioxidant layer composed of tocopherols and carotenoids further blocks the oxidation chain reaction. The synergistic effect of these three layers significantly improves the photostability of the essential oil components.
[0405] Experiment 2: Improving the Loading Efficiency of Essential Oil Components through Separation and Loading Technology Based on Hydrophilicity Differences
[0406] Experimental Objective
[0407] To verify the effect of essential oil component separation and loading technology based on logP value difference on improving the loading efficiency of different hydrophilic essential oil components.
[0408] Experimental materials
[0409] Essential oil ingredients: menthol, borneol, lime oil, patchouli oil, lavender oil, basil, geranium oil, clove oil, eucalyptus oil; plant-derived emulsifiers: saponins, lecithin, protein hydrolysate, sucrose fatty acid esters; carrier materials: sodium alginate, chitosan, calcium chloride, zinc chloride; analytical instruments: high performance liquid chromatography (HPLC), ultraviolet spectrophotometer; standards: standards for the main components of each essential oil.
[0410] Experimental steps
[0411] Determination and grouping of logP values of essential oil components:
[0412] The retention times of each essential oil component were determined by reversed-phase HPLC. The logP values of each component were calculated based on the standard curve. The essential oil components were divided into two groups: hydrophilic components (logP<3): menthol (logP=2.74); hydrophobic components (logP≥3): borneol (logP=3.04), limonene (logP=4.8), patchouli alcohol (logP=4.1), linalool (logP=3.3), eugenol (logP=3.1), and eucalyptol (logP=3.2).
[0413] Preparation of control group (traditional mixed loading method):
[0414] All essential oil components were directly mixed to a total concentration of 10 mg / ml; an emulsifier mixture (0.5% each of saponins, lecithin, protein hydrolysate, and sucrose fatty acid esters) was added; the mixture was homogenized at high speed (10,000 rpm, 10 minutes) to form an emulsion; sodium alginate solution (2%, w / v) was added and mixed thoroughly; the mixture was then added dropwise to calcium chloride solution (2%, w / v) to crosslink into gel beads.
[0415] Experimental group preparation (separation loading method):
[0416] Hydrophilic component loading: Menthol was dissolved in the aqueous phase (containing 2% sodium alginate) at a concentration of 5 mg / ml; Hydrophobic component loading: Borneol and other essential oil components were dissolved in the oil phase (containing 0.5% lecithin) at a concentration of 5 mg / ml; Preparation of biphase microemulsion system: The aqueous phase and oil phase were mixed at a ratio of 1:1, and a composite emulsifier system was added; Temperature gradient treatment: The mixture was treated at 40℃ for 10 minutes, at 60℃ for 5 minutes, and then cooled to 25℃; Gradient crosslinking: The mixture was first crosslinked in 0.5% calcium chloride for 10 minutes, and then transferred to 2% calcium chloride for 20 minutes.
[0417] Load efficiency measurement:
[0418] Collect the gel beads and wash them three times with deionized water; accurately weigh 100 mg of gel beads and add 5 ml of ethanol-water (7:3, v / v) solution; sonicate for 30 minutes and centrifuge (12000 rpm, 15 minutes); take the supernatant and determine the content of each essential oil component by HPLC; loading efficiency (%) = (essential oil content in gel beads / initial amount of added essential oil) × 100%.
[0419] Stability test:
[0420] The prepared gel beads were placed in a constant temperature and humidity chamber at 37℃ and 75% relative humidity; the essential oil content was measured at 0, 24, 48 and 72 hours; the retention rate was calculated as follows: retention rate (%) = (essential oil content after storage / initial essential oil content) × 100%.
[0421] Experimental results
[0422] Table 3. Comparison of loading efficiency of different essential oil components (%)
[0423]
[0424] Table 4. Results of 72-hour storage stability test (%)
[0425]
[0426] Figure 2 A comparison chart showing the loading efficiency of different essential oil components is presented.
[0427] Results Analysis
[0428] Experimental results show that after adopting the separation and loading technology based on differences in hydrophilicity, the average loading efficiency of each essential oil component increased from 71.9% to 95.6%, an increase of 33.0%. Among them, the loading efficiency of the more hydrophobic limonene (logP=4.8) showed the most significant improvement, reaching 43.0%. This is because the separation and loading technology avoids the mutual interference between hydrophilic and hydrophobic components, allowing each component to achieve efficient loading in the most suitable phase environment. Meanwhile, the 72-hour storage stability test showed that the product prepared by the separation and loading method still retained 90.8% of the essential oil content after 72 hours of storage, while the traditional method only retained 55.2%, proving that this technology significantly improves the storage stability of the product while increasing the loading efficiency.
[0429] Experiment 3: Precise control of essential oil release process by multi-layered gel networks
[0430] Experimental Objective
[0431] Verify the precise control effect of the "net-within-a-net" multi-layered gel network structure on the three-stage release mode of essential oil components.
[0432] Experimental materials
[0433] Product of this invention: an essential oil refreshing composition with a complete three-layer structure and a "net within a net" system; Control product A: an essential oil product with only a single-layer ionogel structure; Control product B: a commercially available slow-release essential oil patch; Release medium: artificial sweat (pH 5.5, containing 9g / L sodium chloride, 1g / L lactic acid, and 1g / L urea); Analytical equipment: UV-Vis spectrophotometer, Franz diffusion cell, and constant temperature shaker; Standards: essential oil component standards such as menthol and borneol.
[0434] Experimental steps
[0435] Setup of in vitro release experimental setup:
[0436] The Franz diffusion cell was used, with an effective diffusion area of 2.54 cm²; the receiving cell had a volume of 12 ml and was filled with artificial sweat; the temperature was controlled at 32 ± 0.5℃ (simulating skin surface temperature); and the stirring speed was 300 rpm.
[0437] Sample preparation and installation:
[0438] Cut the three products into 2cm diameter discs; weigh each product precisely and record the essential oil content; fix the sample between the supply and receiving cells of the Franz diffusion cell; ensure that the sample is in full contact with the release medium.
[0439] Timed sampling and analysis:
[0440] Sampling time points: 5, 10, 15, 30, 60 minutes, 2, 4, 6, 8, 12, 16, 20, 24 hours; 1 ml sample was taken each time, and an equal amount of fresh artificial sweat was added at the same time; the total essential oil content was determined at a wavelength of 280 nm using a UV-Vis spectrophotometer; the essential oil concentration was calculated according to the standard curve.
[0441] Release kinetic analysis:
[0442] Calculate the cumulative release rate: Q(%) = (Mt / M∞) × 100%; where Mt is the cumulative release amount at time t, and M∞ is the total amount of drug; plot the release curve and analyze the characteristics of the release stage; use different kinetic models for fitting to determine the release mechanism.
[0443] Release phase division:
[0444] Rapid release phase: 0-15 minutes; sustained release phase: 15 minutes-8 hours; deep release phase: 8-24 hours; calculate the release percentage for each phase.
[0445] Experimental results
[0446] Table 5. Cumulative release rate (%) of the three products at different time points
[0447]
[0448] Table 6. Comparison of three-stage release characteristics
[0449]
[0450] Figure 3 The presentation showed a comparison of essential oil release from the three products.
[0451] Results Analysis
[0452] The experimental results clearly demonstrate the unique three-stage release characteristics of the product of this invention. In the rapid release stage (0-15 minutes), the product of this invention releases 25.2% of the essential oil components, significantly lower than the 53.2% and 48.7% of the control products, thus avoiding the initial burst release phenomenon. In the sustained release stage (15 minutes-8 hours), the product of this invention stably releases 50.1% of the essential oil, while the control products release only 41.3% and 44.1% in this stage. Most importantly, in the deep release stage (8-24 hours), the product of this invention still releases 16.2% of the essential oil, while the control products have almost completely released (only 3.3% and 3.9%).
[0453] This precise three-stage release pattern benefits from a multi-layered gel network structure: the outer ionic cross-linked network controls the initial release rate and prevents explosive release; the middle biphasic microemulsion system provides continuous and stable release; and the inner covalent cross-linked network acts as a deep reservoir to ensure long-lasting release. The gradient cross-linked structure (30-40% on the surface and 70-80% inside) further optimizes the release kinetics, achieving a sustained energizing effect for more than 24 hours.
[0454] The embodiments of the present invention have been described above. However, the embodiments are not limited to the specific implementation methods described above. The specific implementation methods described above are merely illustrative and not restrictive. Those skilled in the art can make more equivalent embodiments under the guidance of the present embodiments, and all of them are within the protection scope of the present embodiments.
Claims
1. A refreshing composition based on plant essential oils, characterized in that, The ingredients include the following components by weight: 20-30 parts menthol, 10-15 parts borneol, 10-15 parts lime oil, 8-12 parts patchouli oil, 8-12 parts lavender oil, 8-12 parts basil, 7-11 parts geranium oil, 3-7 parts clove oil, and 3-7 parts eucalyptus oil. The composition also includes a three-layer composite delivery system, a plant-derived emulsifier composite biphase system, and a photoprotective and antioxidant protective layer; The three-layer composite delivery system includes: an ion gel sustained-release base layer, which is formed by cross-linking natural polysaccharides with multivalent metal ions and has a gradient distribution of cross-linking degree from the surface to the interior; The plant-derived emulsifier composite biphase system includes an aqueous phase and an oil phase, wherein the hydrophilic essential oil component is loaded in the aqueous phase and the hydrophobic essential oil component is loaded in the oil phase; The photoprotection and antioxidant protective layer includes a light shielding layer, a free radical scavenging layer, and an antioxidant layer. The light shielding layer contains a plant-derived light shielding agent, the free radical scavenging layer contains a plant-derived free radical scavenger, and the antioxidant layer contains a plant-derived antioxidant.
2. The invigorating composition based on plant essential oils according to claim 1, characterized in that, The natural polysaccharide is selected from sodium alginate, chitosan and combinations thereof; the multivalent metal ions are selected from calcium ions, zinc ions and combinations thereof.
3. The invigorating composition based on plant essential oils according to claim 1, characterized in that, The crosslinking degree gradient distribution of the ionogel sustained-release base layer is as follows: the surface crosslinking degree is 30-40%, and the internal crosslinking degree is 70-80%.
4. The invigorating composition based on plant essential oils according to claim 1, characterized in that, The plant-derived emulsifiers in the plant-derived emulsifier composite biphasic system are selected from saponins, lecithin, protein hydrolysates, sucrose fatty acid esters, and combinations thereof.
5. The invigorating composition based on plant essential oils according to claim 1, characterized in that, The plant-derived light-shielding agent includes anthocyanins and lycopene; the plant-derived free radical scavenger includes tea polyphenols and rosemary extract; the plant-derived antioxidant includes tocopherols and carotenoids.
6. A method for preparing a refreshing composition based on plant essential oils according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Prepare an essential oil-based invigorating composition; Step 2: Constructing the ionogel sustained-release base layer, including preparing a natural polysaccharide solution, preparing a polysaccharide-essential oil premix system, and forming a gradient cross-linking network; Step 3: Construct a plant-derived emulsifier complex biphase system, including preparing a plant-derived emulsifier complex system, separating and loading essential oil components based on differences in hydrophilicity, forming a biphase microemulsion system, and constructing a multi-layered gel network; Step 4: Add a photoprotective and antioxidant protective layer, including the preparation of plant-derived light-shielding agents, plant-derived free radical scavengers and plant-derived antioxidants, and the construction of a multi-layered photoprotective and antioxidant synergistic structure; Step 5: Product shaping and packaging.
7. The method for preparing the invigorating composition based on plant essential oils according to claim 6, characterized in that, The method for forming a gradient cross-linked network in step 2 includes: adding the polysaccharide-essential oil premixed system dropwise into a low-concentration metal ion cross-linking solution for surface cross-linking for 10-20 minutes, and then transferring it to a high-concentration metal ion cross-linking solution for deep cross-linking for 20-40 minutes.
8. The method for preparing the invigorating composition based on plant essential oils according to claim 6, characterized in that, The method for separating loaded essential oil components based on hydrophilicity differences in step 3 includes: loading hydrophilic essential oil components with logP<3 into the aqueous phase, and loading hydrophobic essential oil components with logP≥3 into the oil phase.
9. The method for preparing the invigorating composition based on plant essential oils according to claim 6, characterized in that, The method for constructing a multi-layered gel network in step 3 includes: using glutaraldehyde to react with amino groups in protein hydrolysates to form a covalent cross-linked network inside the microemulsion droplets, thus constituting a "network within a network" hierarchical system.
10. The application of a refreshing composition based on plant essential oils, characterized in that, It is used in stimulating patches.
Citation Information
Patent Citations
Veterinary drug with kidney strengthening effect
CN102846622A
Laboratory cleaning equipment
CN108687077A
Cited By
Ocimum basilicum flavor essence composition and preparation method thereof
CN121518217A
Method for extracting torreya grandis aril essential oil
CN121852139A